2021
DOI: 10.3389/fmolb.2021.660269
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA TLK1 Promotes Sepsis-Associated Acute Kidney Injury by Regulating Inflammation and Oxidative Stress Through miR-106a-5p/HMGB1 Axis

Abstract: Sepsis is an inflammatory disorder and leads to severe acute kidney injury (AKI). Circular RNAs (circRNAs) have been identified as a critical type of regulatory noncoding RNAs (ncRNAs) that present the important functions in various diseases. In this study, we identified a novel circRNA circTLK1 in the regulation of sepsis-induced AKI. We observed that circTLK1 expression was elevated in the cecal ligation and puncture (CLP) rat model compared with that in the control rats. The urine levels of neutrophil gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…circRNAs can suppress mRNA degradation by sponging miRNAs through forming a ceRNA network [ 17 ]. For example, circTLK1 aggravates sepsis-induced ALI by augmenting oxidative stress and inflammation by the miR-106a-5p/HMGB1 axis [ 29 ]. circ_0091702 sponges miR-545-3p and upregulates THBS2 to mitigate sepsis-related ALI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs can suppress mRNA degradation by sponging miRNAs through forming a ceRNA network [ 17 ]. For example, circTLK1 aggravates sepsis-induced ALI by augmenting oxidative stress and inflammation by the miR-106a-5p/HMGB1 axis [ 29 ]. circ_0091702 sponges miR-545-3p and upregulates THBS2 to mitigate sepsis-related ALI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether circ-Snrk had an effect on the IRI-induced AKI animal model, the lentivirus target for circ-Snrk (shRNA), as well as the negative control lentivirus (shRNA-NC), were purchased from Genepharma (Shanghai, China), Then another 15 Sprague-Dawley rats were used for this experiment and randomly divided into three groups (five rats per group): sham group, AKI + shRNA NC group, and AKI + shRNA group. For AKI + shRNA NC group and AKI + shRNA group, lentivirus was injected into tail vein with 1 × 10 9 TU following with previous study [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pathways include metabolism [55], neutrophil degranulation [56], metabolism of lipids [57], immune system [58], metabolism of proteins [59] and TP53 [60] regulates metabolic genes were linked with progression of T1DM. KDM7A [61], LMNA (lamin A/C) [62], PFKFB3 [63], NEU1 [64], DUSP22 [65], ADORA2B [66], CRTC2 [67], GRN (granulin precursor) [68], CTSD (cathepsin D) [69], IGFBP4 [70], SMYD2 [71], OSM (oncostatin M) [72], INVS (inversin) [73], ANKFY1 [74], SEMA4D [75], PPM1A [76], IFNG (interferon gamma) [77], CTBP1 [78], ATP6 [79], COX2 [80], RPS19 [81], COX1 [82] and TLK1 [83] are potential biomarkers for the detection and prognosis of renal diseases. A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity.…”
Section: Discussionmentioning
confidence: 99%